Deficits in Education Endanger Germany's Innovative Capacity - Heike Belitz; Marius Clemens; Jens Schmidt-Ehmcke; Stephanie Schneider; Axel Werwatz (Weekly Report, 2008)
The innovative capacity of advanced industrial countries is their most important source of prosperity and growth. DIW Berlin has investigated Germany's innovative capacity for the fourth time in an international comparative survey. The survey evaluates the ability of countries to create and transform knowledge into marketable products and services (i.e., innovations) using a system of indicators that provides an overall composite indicator of innovative capacity as well as a detailed profile of strengths and weaknesses. Of the seventeen leading industrial nations investigated under the survey, Germany only ranked 8th, as it did in 2007, thus remaining in the broad middle range. Relative to its most important competitors Germany was unable to improve its position. Sweden, the US, Switzerland, Finland, and Denmark headed up the list. Germany is particularly successful in international markets for new products and services and in its ability to network key participants in the innovation process. Deficiencies in Germany's educational system and in the financing conditions for innovation and the founding of new companies remain the country's two greatest weaknesses. Prospects are dim for the considerable improvement needed in these areas.
Keywords: O30; O38; O57; 330; Innovation system; Composite indicator; Industrialized countries